PENGEMBANGAN MEDIA PEMBELAJARAN POCKET CARD TERHADAP MEMBACA MENULIS PERMULAAN TEMA 7 KELAS 2 SD - nurul annisa; sujarwo (JURNAL PENDIDIKAN DAN PEMBELAJARAN TERPADU (JPPT), 2023)
This development research aims to develop Pocket Card learning media for reading and writing the beginning of theme 7 which is suitable for learning. This research is a type of research and development using the ADDIE development model. In this study, researchers carried out the ADDIE development model only up to the development stage. The instrument used to collect data is a questionnaire or questionnaire containing aspects of the assessment with statement items with the "Yes" and "No" assessment columns given to validators, namely media expert validators, material expert validators and learning expert validators. Of the 20 statement items given to the media expert validator, all statements on the validation sheet received a "Yes" rating. The media expert validator does not provide revision notes. Of the 15 statement items given to the material expert validator, all statements received a "Yes" assessment without any revision notes and of the 5 statement items given to the learning expert validator, all statements also received a "Yes" assessment without any revision notes. Based on the results of the assessments of the three validators, it can be said that the Pocket Card learning media for reading and writing the beginning of theme 7 developed is "Very Appropriate" to be used in the learning process.